6s-2=5s+10

Simple and best practice solution for 6s-2=5s+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6s-2=5s+10 equation:


Simplifying
6s + -2 = 5s + 10

Reorder the terms:
-2 + 6s = 5s + 10

Reorder the terms:
-2 + 6s = 10 + 5s

Solving
-2 + 6s = 10 + 5s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-5s' to each side of the equation.
-2 + 6s + -5s = 10 + 5s + -5s

Combine like terms: 6s + -5s = 1s
-2 + 1s = 10 + 5s + -5s

Combine like terms: 5s + -5s = 0
-2 + 1s = 10 + 0
-2 + 1s = 10

Add '2' to each side of the equation.
-2 + 2 + 1s = 10 + 2

Combine like terms: -2 + 2 = 0
0 + 1s = 10 + 2
1s = 10 + 2

Combine like terms: 10 + 2 = 12
1s = 12

Divide each side by '1'.
s = 12

Simplifying
s = 12

See similar equations:

| 12-.6x=-27 | | (16x+5y)dx+(3x+y)dy=0 | | x*x=-36 | | 2x^3-8x^2-14x= | | 10x=4.09 | | n^3-n-3360=0 | | e^1-7x=9 | | (6-v)(3v-4)=0 | | x=2600 | | x-.2=13000 | | x*x=5 | | 4x+1=25-2x | | 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 | | o^2+0o+-4=0 | | -7=p-5 | | 6s^2+3s=0 | | 802.1-4.82+9= | | y-9=-19 | | 4r^2+30r+10=0 | | 24=4n | | 8(x+12)-288=3x | | 3q+4=2q+10 | | 2x^2+8x=192 | | 8x+35=6x+27 | | n^2+-3n+-40=0 | | 7x+1=52 |

Equations solver categories